2016
DOI: 10.1002/ange.201511881
|View full text |Cite
|
Sign up to set email alerts
|

The Benzyl Moiety in a Quinoxaline‐Based Scaffold Acts as a DNA Intercalation Switch

Abstract: Quinoxaline antibiotics intercalate dsDNAa nd exhibit antitumor properties.H owever,t hey are difficult to synthesize and their structural complexity impedes ac lear mechanistic understanding of DNAbinding.Therefore design and synthesis of minimal-intercalators,u sing only part of the antibiotic scaffold so as to retain the key DNA-binding property,isextremely important. Reported is aunique example of am onomeric quinoxaline derivative of a6 -nitroquinoxaline-2,3-diamine scaffold which binds dsDNAbytwo differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Here we have designed a series of monoquinoxaline based derivatives (Figure C) from the modification of the scaffold 3g (Figure B) . In order to achieve this, two sets of compounds were designed by changing the substituents at C-2 and C-3 positions of the 6-nitroquinoxaline moiety, all of which were subjected to antibacterial evaluation (Figure C).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Here we have designed a series of monoquinoxaline based derivatives (Figure C) from the modification of the scaffold 3g (Figure B) . In order to achieve this, two sets of compounds were designed by changing the substituents at C-2 and C-3 positions of the 6-nitroquinoxaline moiety, all of which were subjected to antibacterial evaluation (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…The structural change of DNA induced by intercalators is reflected in the mobility of supercoiled plasmid DNA in agarose gel . Previously we have shown that compound 3g (with mandatory benzyl moiety) shows gel shift of pBR322 plasmid DNA indicating DNA intercalation . To investigate the structural change of DNA induced by the designed quinoxaline molecules, we have studied the agarose gel shift assay of supercoiled plasmid DNA (pCDNA3.1) by the most potent analogues ( 3a , 3u , and 3q ) and compound 3d , which does not show any antibacterial activity.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations